(untitled) (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Lemuru fish meal can be used as an additional ingredient or supplement in peanut brittle products. This research aims to determine the level of organoleptic preference for peanut brittle from various levels of addition of lemuru fish meat flour. The research method used was experimental with 4 treatments, namely A. level of addition of lemuru fish meal 0% of rice flour, B. level of addition of lemuru fish meal 2.5% of rice flour, C. level of addition of lemuru fish meal 5% from rice flour and D. the level of addition of lemuru fish meat flour is 7.5% of rice flour. The peanut brittle obtained from each treatment was observed for its organoleptic preference level which included appearance, aroma, texture and taste. Organoleptic preference level testing was carried out using a hedonic test by 15 semi-trained panelists. The data obtained were analyzed using the Friedman test and multiple comparison test. The Bayes method was used to determine the best treatment. The results of the research showed that the level of addition of lemuru fish meat flour only affected the level of preference for the taste of peanut brittle produced. The most popular peanut brittle is obtained from lemuru fish meat without adding flour. The next favorite in order is peanut brittle which is obtained from the addition of fish meal at 2.5%, 5% and 7.5%.